Centro para el desarrollo comercial. Emergente (2022)
The study of the urban and architectural characteristics, and the possible rehabilitation measures for large shopping centers have meant that over the years an optimal need has been generated for the development of new mechanisms capable of being fully adaptable to unconventional places that help increase the mechanisms of the region, which makes them the starting point for evaluating their environmental and urban sustainability.